2023
DOI: 10.1094/pdis-05-22-1008-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Fusarium kalimantanense Causing Fusarium Wilt on Banana Tree in Brazil

Abstract: Banana (Musa spp.) is the second most-consumed fruit in Brazil, the fourth-largest producer globally, with 7 million tons in 2021 (IBGE 2021). Studies about the morphological and pathogenic characteristics revealed that the etiology of Fusarium wilt in banana cultivars in Brazil had been related to the Fusarium oxysporum f. sp. cubense (Foc) (E.F. Smith) Snyder and Hansen species (Costa et al. 2015; Cordeiro et al. 2016; Araújo et al. 2017). Phylogenetic studies have shown the existence of distinct genetic lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Recently, the taxonomy of the Fusarium lineages that cause FWB was revised (Maryani et al, 2019). TR4 was considered as the new species F. odoratissimum , Race 2 strains belong to F. phialophorum , F. tardicrescens or F. tardichlamydosporum , while Race 1 strains are present in at least seven species (Czislowski et al, 2021; Maryani et al, 2019; Santos et al, 2022). To determine which lineages or phylogenetic species are present in Cuba and to uncover their genetic diversity, we generated genotyping‐by‐sequencing DArT markers across the 170 Cuban isolates and added these to DArT markers that were previously obtained from 243 additional isolates, comprising 210 isolates from the Americas and the 33 isolates from other regions worldwide (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the taxonomy of the Fusarium lineages that cause FWB was revised (Maryani et al, 2019). TR4 was considered as the new species F. odoratissimum , Race 2 strains belong to F. phialophorum , F. tardicrescens or F. tardichlamydosporum , while Race 1 strains are present in at least seven species (Czislowski et al, 2021; Maryani et al, 2019; Santos et al, 2022). To determine which lineages or phylogenetic species are present in Cuba and to uncover their genetic diversity, we generated genotyping‐by‐sequencing DArT markers across the 170 Cuban isolates and added these to DArT markers that were previously obtained from 243 additional isolates, comprising 210 isolates from the Americas and the 33 isolates from other regions worldwide (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analyses, based on several DNA‐based techniques, have consistently shown that Foc isolates are divided into three major clades, which are further subdivided into eight to 10 lineages (Bentley et al, 1998; Fourie et al, 2009; Groenewald et al, 2006; Maryani et al, 2019; Mostert et al, 2017; Mostert et al, 2022; O'Donnell et al, 1998). These lineages encompassing the various physiological races were recently classified as individual phylogenetic species (Maryani et al, 2019), with TR4 strains classified as Fusarium odoratissimum and strains of Race 1 comprising a suite of seven Fusarium spp., while Race 2 strains belong to F. phialophorum, F. tardicrescens or F. tardichlamydosporum (Czislowski et al, 2021; Maryani et al, 2019; Santos et al, 2022). However, this new nomenclature of FWB‐causing Fusarium species generated controversy, due to concerns about the robustness of the classification, which was based on multi‐locus genotyping data (Mostert et al, 2022; Torres Bedoya et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the taxonomy of the Fusarium lineages that cause FWB was revised (Maryani et al ., 2019). TR4 was considered as the new species F. odoratissimum, Race 2 strains belong to F. phialophorum , F. tardicrescens or F. tardichlamydosporum, while Race 1 strains are present in at least seven species (Maryani et al ., 2019; Czislowski et al ., 2021; Santos et al ., 2022). To determine which species are present in Cuba and to uncover their genetic diversity, we generated genotyping-by-sequencing DArT markers across the 170 Cuban isolates and added these to DArT markers that were previously obtained from 243 additional isolates, comprising 210 isolates from the Americas and the 33 isolates from other regions worldwide (Supporting Information Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Clade 3 included a group of 29 F. oxysporum isolates from Brazil, Colombia, Nicaragua, and Perú (Table S3), which did not cluster with any of the representatives of the previously defined lineages. Finally, a small group of isolates formed clade 4, encompassing the F. sangayamense and F. kalimantanense lineages, which are endemic to Indonesia and non-pathogenic on 'Gros Michel' and 'Grand Naine' (Maryani et al, 2019), although the latter was recently reported to infect "Silk" (AAB) bananas in Brazil, which is indicative for Race 1 (Santos et al, 2022). The great majority (95%) of the Cuban isolates grouped in the lineages corresponding with the species F. tardichlamydosporum and F. tardicrescens in clade 2, whereas only 5% grouped in the F. purpurascens lineage of clade 1.…”
Section: Fusarium Spp Causing Fwb In Cuba Are Genetically Diversementioning
confidence: 99%